Hімецька національна меншина Xарківщини в 1920-х роках - Філатова, О.Є. (Культура народов Причерноморья, 2013)
Стаття присвячується вивченню проблем соціально-економічного та політичного розвитку
німецької національної меншини Харківщини в 20-і рр. ХХ століття, в умовах нової етнічної політики. У
дослідженні вперше комплексно проаналізовано, заходи які проводилися органами влади в рамках
політики «коренізації», щодо німецького населення краю, їх основні цілі та наслідки. Велику увагу
приділено створенню національних адміністративно-територіальних одиниць даної групи населення,
проблеми їх існування.
Ключові слова: національна меншина, національна політика, коренізація Статья посвящается изучению проблем социально-экономического и политического
развития немецкого национального меньшинства Харьковщины в 20-е гг. ХХ века, в условиях новой
этнической политики. В исследовании впервые комплексно проанализированы, мероприятия проводимые
органами власти в рамках политики «коренизации», в отношении немецкого населения края, их основные
цели и последствия. Большое внимание уделено созданию национальных административно-
территориальных единиц данной группы населения, проблемы их существования.
Ключевые слова: национальное меньшинство, национальная политика, коренизация The article is devoted to the study of the problems of socio-economic and political development of the
German minority in Kharkiv 20s. Twentieth century, in the introduction to the Soviet Union of a new ethnic
politics. In the first study to comprehensively analyzed, activities undertaken within the framework of
government policy of "indigenization", in respect of the German population of the region, their main purpose
and effect. Much attention is paid to the creation of national administrative units in the population, the problem
of their existence. We also consider the question of social stratification among ethnic Germans in the Kharkiv
region, their integration into the regional economy. Raises the issue of retraction of the latter in political life
through their involvement in the governance apparatus of Kharkiv. In the context of the study, revealed the
purpose of Soviet ethnic policy, which consists in submission of national processes tasks of internal policies,
which resulted in the elimination of the usual for the German national group of social and economic structure,
the decline of their economic activities. The result of which it became a mass movement in exile considered an
ethnic minority.
Keywords: national minority, a national policy, korenyzatsyya